Memorandum of Understanding between Northern University Bangladesh (NUB) and Brac University (2011) - Brac University; Northern University Bangladesh (NUB) (Brac University and Northern University Bangladesh (NUB), 2019)
The agreement made between Northern University Bangladesh (NUB) and Brac university for implementation of an Integrated Library System (lLS) using KOHA at NUB Library.